A Hybrid Copper:Tungsten Suboxide Window Electrode for Organic Photovoltaics. (31st October 2014) - Hutter, Oliver S.; Hatton, Ross A.
<x xml:space="preserve">Abstract</x> A new type of window electrode for organic photovoltaics (OPVs) based on an ultra‐thin bilayer of copper and amorphous tungsten suboxide, which derives its remarkable optical and electrical properties from spontaneous diffusion of copper into the oxide layer. As the window electrode in efficient inverted OPVs, this unpatterned electrode is shown to perform as well as indium‐tin oxide glass. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>